Cancer cluster among young Indian adults living near power transmission lines in Bom Jesus do Tocantins, Pará, Brazil Agrupação de casos de câncer em adultos jovens indígenas residindo nas proximidades de linhas de transmissão de alta tensão elétrica em Bom Jesus do Tocantins, Pará, Brasil - Sergio Koifman; Iara Ferraz; Trajano S. Viana; Carmen L. P. Silveira; Maria T. D. Carneiro; Rosalina J. Koifman; Paula N. Sarcinelli; Rita de Cássia O.C. Mattos; Jaime S. Lima; Jefferson J.O. Silva; Josino C. Moreira; Maria de Fátima A. Ferreira; et al. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
A case study was carried out to explore the occurrence of a cancer cluster in 1992 among young indian adults living in an Amazonian village near two 500 kV power transmission lines that began operating a decade ago. Current blood levels of DDT and organophosphorus pesticides and metal levels in hair samples were measured. Extremely low magnetic field exposure was determined during current daily activities carried out by the Indian villagers. Taking into account the cancer incidence rates in different Brazilian cities, the probability of the occurrence of this cluster by chance was considered remote (p< 0.003, Poisson distribution). High blood levels of p,p'-DDT (median levels ranging from 26 to 58 ppb) were observed. As a whole, this community showed a pattern of low exposure to organophosphorus pesticides, and high recent exposure was only observed in a few blood samples. Continuous exposure to extremely low electromagnetic fields originated in the power transmission lines (which reached 95.0 mG under the lines) was observed on several opportunities during daily activities carried out by Indian villagers. Further observational studies should evaluate the interaction between exposure to extremely low electromagnetic fields and prior exposure to tumor initiators in cancer development. Um estudo de caso foi desenvolvido para avaliar a ocorrência de um agrupamento de casos de câncer em 1992, que se verificou em adultos jovens indígenas vivendo em aldeia na Amazônia, situada nas proximidades de duas linhas de transmissão de 500 kV, as quais começaram a operar em 1982. Determinaram-se os níveis sangüíneos atuais de DDT e pesticidas organofosforados, assim como a presença de metais em amostras de cabelo. A exposição a campos eletromagnéticos de freqüência extremamente baixa foi determinada durante diversas atividades diárias desenvolvidas pelos indígenas. Considerando-se a incidência de câncer em diferentes cidades brasileiras, a probabilidade de ocorrência ao acaso deste agrupamento de casos foi considerada remota (p<0,03, distribuição de Poisson). Níveis elevados de p,p'-DDT (mediana variando entre 26 e 58 ppb) foram observados nas amostras estudadas. A exposição contínua aos campos eletromagnéticos de freqüência extremamente baixa, a qual atingiu 95 mG abaixo das linhas de transmissão, foi observada em diversas oportunidades durante atividades diárias desenvolvidas pelos indígenas. Estudos observacionais futuros deveriam analisar a interação da exposição aos campos eletromagnéticos de freqüência extremamente baixa (50-60 Hz) subseqüente à exposição a agentes de iniciação tumoral no desenvolvimento de neoplasias.